2011
DOI: 10.1021/jo200651b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis ofN-Arylisatins by the Reaction of Arynes with Methyl 2-Oxo-2-(arylamino)acetates

Abstract: N-Arylisatins are efficiently prepared by the reaction of 2-oxo-2-(arylamino)acetates and arynes under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(21 citation statements)
references
References 25 publications
(35 reference statements)
0
21
0
Order By: Relevance
“…[9] The direct arylation of free N-H isatins with aryl boronic acids is a useful approach for the preparation of N-arylisatins. [11] Because N-arylisatins have exhibited impressive biological properties and because they can be readily used as key intermediates for the synthesis of potent drugs (Scheme 2), [10c,10d] the design of general and direct approaches for the preparation of N-arylisatins is highly desirable. More recently, Larock et al developed a F --promoted reaction of arynes with methyl 2oxo-2-(arylamino)acetates to afford various N-arylisatins in good yields [see Eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] The direct arylation of free N-H isatins with aryl boronic acids is a useful approach for the preparation of N-arylisatins. [11] Because N-arylisatins have exhibited impressive biological properties and because they can be readily used as key intermediates for the synthesis of potent drugs (Scheme 2), [10c,10d] the design of general and direct approaches for the preparation of N-arylisatins is highly desirable. More recently, Larock et al developed a F --promoted reaction of arynes with methyl 2oxo-2-(arylamino)acetates to afford various N-arylisatins in good yields [see Eq.…”
Section: Introductionmentioning
confidence: 99%
“…(3) in Scheme 1]. [11] Because N-arylisatins have exhibited impressive biological properties and because they can be readily used as key intermediates for the synthesis of potent drugs (Scheme 2), [10c,10d] the design of general and direct approaches for the preparation of N-arylisatins is highly desirable. In recent years, the transitionmetal-catalyzed oxidative amidation of aldehydes (or from alcohols by dehydrogenation) with amines has proved to be a powerful and environmentally benign strategy for the preparation of amides.…”
Section: Introductionmentioning
confidence: 99%
“…63 g) gave 3a (eluent: heptane-AcOEt 80:20) in 90% yield (0.60 g) as an orange powder: mp 137 °C (lit 53. 136-139 °C); 1 H NMR (CDCl 3 ) δ 6.90 (d, 1H, J = 8.0 Hz), 7.17 (td, 1H, J = 7.6 and 0.9 Hz), 7.40-7.59 (m, 6H), 7.70 (dd, 1H, J = 7.4 and 1.4 Hz);13 C NMR (CDCl 3 ) δ 111.4 (CH), 117.7 (C), 124.4 (CH), )acetophenone (2b, 0.86 g) gave 3b (eluent: heptane-AcOEt 80:20) in 67% yield (0.60 g) as an orange powder: mp 178 °C; 1 H NMR (CDCl 3 ) δ 6.98 (dt, 1H, J = 8.0 and 0.75 Hz), 7.19 (td, 1H, J = 7.5 and 0.8 Hz), 7.37-7.52 (m, 5H), 7.57 (td, 1H, J = 7.8 and 1.4 Hz), 7.59-7.64 (m, 2H), 7.72 (ddd, 1H, J = 7.5, 1.4 and 0.6 Hz), 7.74-7.79 (m, 2H);13 C NMR (CDCl 3 ) δ 111.4 (CH), 117.7 (C), 124.5 (CH), 125.8 (CH), 126.4 (2CH), 127.3 (2CH), 128.0 (CH), 128.8 (2CH), 129.1 (2CH), 132.1 (C), 138.5 (CH), 140.1 (C), 142.0 (C), 151.8 (C), 157.6 (C), 183.0 (C).…”
mentioning
confidence: 99%
“…Fortunately, 15% yield of desired N-methyl isatin (2 a) was obtained (Table 1, entry 1). The screenings of oxidants showed that TBHP was the most efficient oxidant, allowing the transformation of indoline 1 a to isatin 2 a in 25% ( 8). Further screen of the reaction conditions showed that the use of amount of catalyst had a major influence on this oxidation (Table 1, entries 9-11), and the reaction performed well in the presence of 20 mol % of Cu (OAc) 2 , providing a satisfying 60% yield of 2 a (Table 1, entry 10).…”
Section: Resultsmentioning
confidence: 99%